Nurturing Excellence: Exploring the Level of Professional Development Strategies for Quality Assurance in a Multi-Campus Higher Education Institution - De Ramos, Lovella C.; Codilla Jr. , Leo L. (Future Science / FSH-PH Publications, 2024)
n higher education, professional development plays a crucial role in ensuring the quality of teaching and learning. This study examines the level of professional development in quality assurance among faculty members of a multi-campus higher education institution. The study's objective was to assess the level of quality assurance professional development strategies. Quantitative data were collected using a survey questionnaire. Weighted mean was employed for data analysis. The study contributes to knowledge by revealing varying effectiveness across professional development strategies. The participants' level of agreement on the key components of professional development initiatives, the faculty members generally agree on the effectiveness and importance of needs assessment, relevance and customization, pedagogical training, and evaluation and feedback. Based on the findings, the study recommends reinforcing faculty engagement strategies, tailoring professional development programs, addressing workload challenges, and leveraging existing opportunities. The findings of this study enrich the understanding of the interplay between professional development and quality assurance in higher education, providing valuable insights for educational institutions to enhance the quality of teaching and learning.